PENGARUH RETURN ON ASSET (ROA) DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM PADA PT AGUNG PODOMORO LAND TBK PERIODE 2013-2022 - Widia Ningsih, Tasya; Karmiyati, Sari (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of Return on Asset (ROA) and Debt To Equity Ratio (DER) On Share Prices at PT. Agung Podomoro Land Tbk for the 2013-2022 period. The method in this research uses quantitative descriptive analysis. The analytical methods used in this research are Descriptivw Test, Classical Assumption Test, Multiple Linear Regressiion Test, Determinant Coefficient Test, T Test (Partial) and F Test (simultaneous). The result of this study show that the variable Return On Asset (ROA) has a T count of 1.723 < 2.6462 with significance obtained by ROA of 0.129 > 0,05 so it can be as parcial ROA variable has no effect on stock prices. Debt to equity ratio (DER) has a T value of 1.899<2.36462 with a significance of 0.099>0.05 can be concluded as parcial the DER variable has ni effect in stock prices. The return on asset and debt to equity ratio variable obtained and F count of 2.702 and F table of 4.74 with significance level of 0.135, > 0.05 can be concluded so it can be concluded that the ROA and DER variables simultaneously hav no effect on stcok prices.